2011
DOI: 10.1210/en.2011-1485
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Metformin-Induced Secretion of Glucagon-Like Peptide-1 from the Intestinal L Cell

Abstract: Glucagon-like peptide-1(7-36NH2) (GLP-1) is secreted by the intestinal L cell in response to both nutrient and neural stimulation, resulting in enhanced glucose-dependent insulin secretion. GLP-1 is therefore an attractive therapeutic for the treatment of type 2 diabetes. The antidiabetic drug, metformin, is known to increase circulating GLP-1 levels, although its mechanism of action is unknown. Direct effects of metformin (5-2000 μm) or another AMP kinase activator, aminoimidazole carboxamide ribonucleotide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 67 publications
(76 reference statements)
5
131
1
2
Order By: Relevance
“…These data confirmed that metformin-induced increase in GLP-1 levels is independent of DPP-4 inhibition after a meal 82,83 . The mechanisms of action explaining why metformin may promote GLP-1 secretion from L cells are rather complex 84 . A recent study demonstrated that metformin protects against lipoapoptosis (possibly by blocking JNK2 activation), and enhances GLP-1 secretion from GLP-1-producing cells in vitro 85 .…”
Section: Potential Synergistic Activitymentioning
confidence: 99%
“…These data confirmed that metformin-induced increase in GLP-1 levels is independent of DPP-4 inhibition after a meal 82,83 . The mechanisms of action explaining why metformin may promote GLP-1 secretion from L cells are rather complex 84 . A recent study demonstrated that metformin protects against lipoapoptosis (possibly by blocking JNK2 activation), and enhances GLP-1 secretion from GLP-1-producing cells in vitro 85 .…”
Section: Potential Synergistic Activitymentioning
confidence: 99%
“…At the same time, there were reports of a favorable therapeutic effect of the association of metformin and GLP-1 preparations [26], and that of a certain role of microbiota (a set of microbes in the intestine) [9].…”
Section: том 13 № 5 2017mentioning
confidence: 99%
“…GLP-1 levels (not GIP or péptideo YY), are increased in obese subjects and diabetic treated with metformin, and this increase is not related to the inhibition of DPP-4, but probably with the muscarinic acetylcholine receptor [17]. Autophagy has implications in metabolism, particularly in cases of energy deficiency and has implications on turnover and function of mitochondria and endoplasmic reticulum.…”
Section: Antidiabetic Action-mechanism Of Actionmentioning
confidence: 99%